Experimental and finite element studies of creep and creep crack growth in P91 and P92 weldments - Saber, Mohammed (2011)
P91 and P92 steels are two ASTM grades of steel which have been used in high temperature applications, such as fossil-fuelled power stations, nuclear power stations and chemical plants. Operating under creep conditions, i.e. high temperature and/or high stress, the welds made from these steels are potential failure locations and, therefore, life limiting for the entire plant. In this thesis, the results of creep and creep crack growth (CCG) tests, which were carried out on P91 and P92 welds, are reported. These tests were carried out on welds constituents, i.e. parent materials (PM) and weld metal (WM), and across-welds, for the P91 material at 650°C and for the P92 material at 675°C. For the cross-weld tests, interest was focused on the Type IV region, a narrow zone at one end of the heat affected zone (HAZ) at the side of the PM. Also reported, in this thesis, are the results of the Finite Element analyses for predicting the creep and creep crack growth in the P91 and P92 materials.